2019
DOI: 10.1101/629584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PROMO: An interactive tool for analyzing clinically-labeled multi-omic cancer datasets

Abstract: BackgroundAnalysis of large genomic datasets along with their accompanying clinical information has shown great promise in cancer research over the last decade. Such datasets typically include thousands of samples, each measured by one or several high-throughput technologies ('omics') and annotated with extensive clinical information. While instrumental for fulfilling the promise of personalized medicine, the analysis and visualization of such large datasets is challenging and necessitates programming skills a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…To train a molecular classifier for predicting melanoma subgroups, we used the expression levels of the 2000 most variable genes on the set of 469 melanoma samples. We used Matlab's implementation (R2019a) (accessed through PROMO [54]) to grow a classification tree using a curvature test as the method for splitting predictors [55,56]. The training procedure consisted of two steps.…”
Section: Training Of a Gene Expression-based Decision Tree Classifiermentioning
confidence: 99%
“…To train a molecular classifier for predicting melanoma subgroups, we used the expression levels of the 2000 most variable genes on the set of 469 melanoma samples. We used Matlab's implementation (R2019a) (accessed through PROMO [54]) to grow a classification tree using a curvature test as the method for splitting predictors [55,56]. The training procedure consisted of two steps.…”
Section: Training Of a Gene Expression-based Decision Tree Classifiermentioning
confidence: 99%
“…To investigate the upstream transcription factors that modulate the KTN1 gene, we predicted transcription factors that might bind to the KTN1 promoter by the PROMO database (http://algge n.lsi.upc.es/cgi‐bin/promo_v3/promo/promoinit.cgi?dirDB = TF8.3) to screen for known transcription factor binding sites 21 . The score from random expectation (RE) analysis identified the top ranked genes as NR3C1 , YY1 , and ESR1 (conforming to RE equally ≥ 2 & RE query ≥ 2, Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the upstream transcription factors that modulate the KTN1 gene, we predicted transcription factors that might bind to the KTN1 promoter by the PROMO database (http://algge n.lsi.upc.es/cgibin/promo_v3/promo/promoinit.cgi?dirDB = TF8.3) to screen for known transcription factor binding sites. 21 The score from random expectation (RE) analysis identified the top ranked genes as NR3C1, YY1, and ESR1 (conforming to RE equally ≥ 2 & RE query ≥ 2, Figure 1C). Next, quantitative real-time reverse transcription (qRT-PCR) analysis showed that knockdown of NR3C1 using NR3C1 siRNA oligonucleotides (siNR3C1) had no significant effect on the regulation KTN1 expression compared with the negative control group (siNC).…”
Section: Yy1 Is a Potential Upstream Transcription Factor Of Ktn1 In ...mentioning
confidence: 99%
“…The problem of data integration in computational biology is far from having a consolidated and shared solution. Many long-standing obstacles are still far from being overcome, and the increasing availability of data [e.g., TCGA, ( 46 )] and computational tools [see for instance ( 47 51 ) and https://github.com/mikelove/awesome-multi-omics ], also interactive [e.g., ( 52 )], is raising new issues that need to be addressed. In fact, not only are existing datasets still lacking standardization protocols to deal with their complexity and heterogeneity, but also the reliability, reproducibility and interpretability of new computational methods are emerging as urgent and relevant questions ( 53 ).…”
Section: Discussionmentioning
confidence: 99%